The incidence of subsequent pregnancies in women enrolled in the DolPHIN 2 studies - Marshall, Amanda (Department of Public Health and Family Medicine, 2025)
Background Inadequate safety and efficacy data for medications during pregnancy, particularly for antiretroviral therapy (ART) regimens, stems from the exclusion of pregnant and postpartum women from clinical trials. Despite global efforts, challenges persist in enrolling this population. In the context of antiretroviral therapy, (ART) the shift from efavirenz (EFV) to dolutegravir (DTG) as the World Health Organization-recommended (first-line regimen) occurred with limited pregnancy data. In some clinical trials, becoming pregnant resulted from withdrawal from the trial, emphasizing the ongoing challenges in including pregnant women in trials. Furthermore, longer term follow-up beyond the duration of trials has been lacking. The objective of this secondary analysis is to provide an interim pathway, of retaining women who subsequently become pregnant and obtaining comprehensive pregnancy data, allowing pregnant women to continue participating in clinical trials. However, evidence on the incidence of subsequent pregnancies among women in such trials is limited and thus we aim to describe it. Methodology This secondary analysis included data from the 250 women (South Africa n=114, Uganda n=135) who met the intention to treat (ITT) criteria in the DolPHIN-2 study and were actively followed up over time. This study focuses on describing the incidence of subsequent pregnancies in a cohort of women enrolled in the DoLPHIN-2 randomized trial and its observational extension study D2 TRIO. The aim of this trial was to explore the safety and efficacy of DTG in pregnant women aged ≥18 years of age, presenting late (≥28 weeks gestational age) for antenatal care. Women were randomised 1:1 to receive DTG or EFV. Data from South Africa and Uganda collected between January 22, 2018, and September 5, 2023, were analysed descriptively. Results This secondary analysis included data from the 250 women (South Africa n=114, Uganda n=135) who met the intention to treat (ITT) criteria in the DolPHIN-2 study and were actively followed up over time. Within this cohort of women, 21% (n=53) experienced at least one subsequent pregnancy, with 7% (n=18) during the clinical trial and 14% (n=34) during the observational extension study. A higher proportion of subsequent pregnancies occurred in the EFV arm (57%, n=30) and at the Uganda site (58%, n=31) compared to the South African site (42 %, n=22). Characteristics of women with subsequent pregnancies revealed a majority being multigravida (87%, n=46), unmarried (90%, n=40), with a high school education (70%, n=33), and unemployed (57%, n=25). Among women with outcome data, 66% (n=23) had a live birth, 11% (n=4) had a termination of pregnancy, and most infants had a normal birth weight (90%, n=19). Conclusion This secondary analysis demonstrated that a high proportion of women had a subsequent pregnancy during the study period. There are calls for pregnant women to be involved in more safety and efficacy medications studies to broaden medication availability to this population. In the interim, instead of excluding women who because subsequently pregnant from clinical trials we recommend that they are retained. This study demonstrates that there may be sufficient numbers who have subsequent pregnancies, who typically would have been excluded, who can shed light on valuable early pregnancy information we would not otherwise have access too.